Religious Fundamentalism, Satisfaction with Life and Posttraumatic Stress Symptoms Intensity in a Polish Sample of People Living with HIV/AIDS - Oniszczenko, Wlodzimierz (Journal of religion and health, 2019)
We investigated the relationship between religious fundamentalism, satisfaction with life and the intensity of posttraumatic stress symptoms in people living with HIV/AIDS. The study was conducted on 283 adults, including 242 HIV-positive patients and 41 individuals with AIDS, aged from 20 to 74. Religious fundamentalism was positively correlated with age and posttraumatic stress symptoms intensity. Negative correlation between satisfaction with life and posttraumatic stress intensity was also found. Religious fundamentalism and satisfaction with life accounted for 34% of the variance in posttraumatic stress symptoms intensity. The level of patients' education mediated the relationship between religious fundamentalism and the posttraumatic stress symptoms intensity.